Qualities of African business leaders - Chown, Davin Loudon (My University, 1994)
The aim of this research was to investigate the perceived qualities of African Business leaders and develop a tentative model of African leadership. In-depth interviews were conducted with a sample of branch regional and senior managers of The African Bank Limited. The results of the data analysis indicated that there are significant diferences in the approaches to management and leadership that exist between adherents to conventional western management paradigisms, and those that adopt a more traditional Afrocentric approach. In addition, the themes and construents that emerged were cross-referenced with those that emerged from the literature study. [Abbreviated Abstract. Open document to view full version]
A research report submitted to the Faculty of Business Administration, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Management (Human Resources) 1994.
Keywords: Executives, Black--Africa.; Executives, Black--South Africa.; Management--Africa.; Management--South Africa.; Leadership